Experts in crisis: The wide spectrum of advisors for coping with extreme events - Verena Brinks; Oliver Ibert (International Journal of Disaster Risk Reduction, 2023)
This paper offers a typology of different groups of “experts” in relation to crisis. While decision-making and leadership are frequently analysed in crisis research, the role of experts who offer advice in crisis is widely underexplored in social scientific research. Based on qualitative interviews, we distinguish between the trouble shooter, the emergency expert, the situative expert, the accidental expert and the trusted advisor. Each of the respective types differs with respect to the specific contribution in dealing with crisis (in terms of expertise in or for crisis), the point in crisis when they are usually called for assistance, as well as their relationship to decision-makers. The proposed typology provides insights into the diversity of experts involved in crisis response and demonstrates the influence expert advisors have on decision-makers during, but also before and after a crisis.
Keywords: 300; Experts; Advice; Crisis; Acute crisis; Pre-crisis; Post-crisis